A Scanning Electron Microscopic Study on the Appendage Morphology of Astacus leptodactylus (Eschscholtz, 1823) and Pacifastacus leniusculus (Dana, 1852) (Crustacea: Decapoda: Astacoidea) - Harlioglu, Muzaffer Mustafa (Soc Chilena Anatomia, 2008)
This study compares the morphology of rostrum, pereipods 1,2,4 and mouthparts of juvenile Astacus leptodactylus with those of Pacifastacus leniusculus. Differences in morphology were observed, in particular with regard to the mouthparts e. g. including setal armature and number of teeth on the mandible. In general, the shape of the rostra in the two species is similar in that both taper to a point with a pair of sharp spines distally. Laterally the rostrum of A. leptodactylus is bordered by a regular row of setae, which is not so well defined in P. leniusculus. The observations also showed that in addition to an increase in size, changes in morphology in the feeding apparatus between the developmental stages of the two species were present. It was concluded that both species have similar rostra, but different setal patterns and there are differences between the two species in the armature of mouthparts as development progresses. Therefore, important differences in the morphology of mouthparts between P. leniusculus and A. leptodactylus and in the different stages of the species might cause a difference in the feeding behavior and food choice of the species.
Estudio en microscopio electrónico de barrido sobre el apéndice morfológico del Astacus leptodactylus (Eschscholtz, 1823) y Pacifastacus leniusculus (Dana, 1852) (Crustacea: Decapoda: Astacoidea)
Keywords: Appendages; Astacus; Crayfish; Mouthparts; Pacifastacus; Scanning electron microscope